Early Soft Tissue Response to Immediate Monotype Zirconia Implant: A Metal-Free Restoration - Scaringi, Riccardo; Franchina, Alessio; Fiorillo, Luca; Galletti, Fulvia; Stefanelli, Luigi; Di Carlo, Stefano; De Angelis, Francesca (European Journal of General Dentistry, 2024)
Zirconia in dentistry (zirconium oxide) is an excellent substitute for metal in creating bridges or crowns on both natural teeth and implants and for dental implant fabrication instead of titanium alloys. This case report aims to show the features of zirconia dental implants and prosthodontic restorations to oral soft tissues. Three monotype immediate zirconia implants were placed at the time of tooth extraction. The residual socket gap was treated only by establishing a collagen sponge to stabilize the natural blood clot. Three single zirconia crowns were cemented after 2 months of healing. After 3 years of follow-up, clinical and radiographic stability was demonstrated, confirming the zirconia implants' excellent soft tissue and osseointegration. A zirconia cutback was planned to improve the esthetic result of the whole crown. After 3 years of follow-up visits, clinical and radiographic stability confirmed the optima soft tissue and osseointegration outcome of zirconia implants. Zirconia implants are a valid alternative to titanium implants for treating partial edentulism.
Keywords: zirconia; monotype zirconia implants; soft tissue; cut-back; metal-free restoration